Effects of nano-enhanced phase change material and nano-coated on the performance of solar stills. (October 2021) - Shoeibi, Shahin; Kargarsharifabad, Hadi; Rahbar, Nader
Highlights: The solar stills with anthracite bed, nano-coated and nano-enhanced PCM were investigated. CuO nanoparticles was more effective to improve the melting of paraffin wax. The freshwater yield of CSSA-NA-NP2 and CSSA-NA-NP4 were improved by 55.8% and 49.5%, respectively. Environmental, exergoeconomic and cost of water production analysis were studied. Abstract: Solar desalination is a widely used system for producing drinking water from solar energy. Freshwater production with renewable energy and without environmental pollution are the benefits of using solar still in addition to being cost-effective. This study aimed to enhance the performance of solar desalination using porous media, nano-enhanced phase change material, and nano-enhanced absorption (nano-coated). The anthracite media was placed in saline water to increase the absorption of solar energy. CuO and Al2 O3 nanoparticles at concentrations of 0.1 and 0.3 wt% were mixed in paraffin wax to increase the thermal properties of phase change material (NEPCM) and poured into 12 copper pipes located on the anthracite. CuO nanoparticles were dispersed in black paint and covered on the copper pipes so that the thermal conductivity of black paint increase. The results indicated that the productivity of the solar stills improved by 55.8% and 49.5% using CuO and Al2 O3 nano-enhanced PCM at a concentration of 0.3 wt% and CuO nano-coated, respectively. Additionally, the added CuO and Al2 O3 nanoparticles at 0.1 wt% reduced the melting point by 2.1 °C and 1.8 °C, respectively. The CPLs of the solar stills were equal to 0.1$/L and 0.104$/L using CuO and Al2 O3 nano-enhanced PCM at a concentration of 0.3 wt% and nano-coated, respectively. Moreover, nano-coated increased the water production rate of the solar still by about 5.7%.